Hubungan Dukungan Keluarga dengan Penggunaan Alat Kontrasepsi pada Perawat di Rsu Islam Cawas - Sawitri, Endang; Apriana, Yuyun; Marwanti, Marwanti; Mawardi, Mawardi (TRIAGE Jurnal Ilmu Keperawatan, 2023)
Nurses are health workers who work in hospitals. Nurses of childbearing age are advised to use contraception to space their births to support performance. Husband's support is very necessary in making the decision to use contraception of choice, especially for nurses at RSI Cawas, most of whom are couples of childbearing ages so that birth spacing can be arranged and does not burden the nurses at work due to frequent pregnancies. Contraception will not work without cooperation between husband and wife and without trust between each other. The coverage of active family planning participants in Klaten Regency in 2020 was 152,764 (78.4%), an increase compared to 2019 of 74.8%. The aim of this research was to determine the relationship between family support and the use of contraceptives among nurses at RSU Islam Cawas. Research method: analytical descriptive research with a cross sectional approach. The research sample was all nurses who were classified as women of childbearing age at RSU Islam Cawas Klaten. The sampling technique uses total sampling. The total sample was 48 respondents. The data collection instrument uses a questionnaire. Bivariate statistical tests use chi square. The research results showed that the characteristics of the respondents in this study were an average age of 33.27 years and an average of 2 children, most of them had a DIII nursing education (60.4%), and the contraceptive method used was modern (29.2%). Family support in the use of contraceptives is mostly good (37.5%), most of the nurses use contraceptives (68.8%). The results of bivariate analysis obtained a p value of 0.028 (p < 0.05). The conclusion of this research is that there is a relationship between family support and the use of contraceptives among nurses at RSU Islam Cawas.